(untitled) (Herald of the National Children’s Medical Center, 2025)
Surgical correction of hypospadias in children is accompanied by significant pain, which requires reliable analgesia. Combined anesthesia — a combination of general and regional anesthesia — helps to reduce pain, reduce the use of narcotic analgesics and minimize side effects.